Mitigating Procurement Fraud Risk at Universitas Khairun, a Higher Education Institution in Indonesia: A Comprehensive Approach Using the Fraud Pentagon Theory - Aswar, Muhammad; Jabid, Abdullah W; Fahri, Johan (Cita konsultindo, 2024)
This study analyses the influence of Procurement Committee Quality, Procurement Environment, Risk Assessment, and Procurement Systems and Procedures on fraud prevention efforts in procuring goods and services at Universitas Khairun. A sample of 57 respondents, consisting of leaders, treasurers, and financial and procurement staff from supplier companies, was used in this research. The analysis was conducted using the multiple linear regression method processed through SPSS version 27.0. The results showed that the Procurement Environment and Procurement System and Procedures significantly influence preventing fraud. In contrast, the Procurement Committee Quality and Risk Assessment had no significant effect. These findings emphasise that creating a conducive procurement environment and improving procurement systems and procedures are key to reducing the risk of fraud at Universitas Khairun. This study provides important contributions for universities and other higher education institutions in designing better procurement policies to minimise fraud.